Cost Variation Study of Various Brands of Oral Fluoroquinolones Available in India: An Economic Perspective - Pallav Hetawal; Sapna More; Kamayani Gupta; Pooja S. Mishra (Universitas Padjadjaran, Indonesia, 2022)
Fluoroquinolones are broad-spectrum antibacterial for treating respiratory tract, intra-abdominal, urinary tract, pelvic, joint, bone, soft tissue, and skin infections. The economic burden on patients affects compliance in developing countries like India. Therefore, the prices of drugs should be controlled effectively. Hence, this study was done to assess the cost variation of branded oral fluoroquinolones available in India compared with generic counterparts. The maximum and minimum cost of oral fluoroquinolones (INR per 10 tablets) of the same strength and dosage form manufactured by different companies was obtained from Drug Today April to July 2021 Volume 1, MIMS, and 1mg.com. The cost ratio and the percentage cost variation of individual drug brands were calculated. Prices of generic fluoroquinolones from the Jan Aushadhi scheme (JAS) were compared with branded drugs. Of 11 different oral fluoroquinolones, levofloxacin 500 mg had the highest percentage variation of 11.100%, and three formulations marketed by a few manufacturers have a percentage reduction of less than 100%. Of 23 different combinations available as 33 different dosages, the highest cost variations were observed in Norfloxacin 400 mg plus tinidazole 600 mg combination (1317%). When compared, some generic fluoroquinolones available under JAS were not cheaper than the minimum cost of their branded counterparts. Wide variation in the cost of the different brands of the same oral fluoroquinolones manufactured by other companies was observed. This adds to the economic burden for the patients. Hence, stakeholders should aim to decrease the cost variation among different brands while maintaining therapeutic efficacy